2009
DOI: 10.1093/bioinformatics/btp480
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-guided inference of domain–domain interactions from incomplete protein–protein interaction networks

Abstract: Motivation: Protein-protein interactions (PPIs), though extremely valuable towards a better understanding of protein functions and cellular processes, do not provide any direct information about the regions/domains within the proteins that mediate the interaction. Most often, it is only a fraction of a protein that directly interacts with its biological partners. Thus, understanding interaction at the domain level is a critical step towards (i) thorough understanding of PPI networks; (ii) precise identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…In order to identify more potential canine Ipr1 binding partners, we discarded those with repeated gene names. Since two domains are more likely to have similar GO terms if they are interacting [35], each candidate proteins' GO annotation terms were checked based on the Ipr1's cellular location and its role in biological processes. Those with a GO annotation term of nuclear and terms of transcription/regulation of transcription/apoptosis or child terms of these annotations were kept.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify more potential canine Ipr1 binding partners, we discarded those with repeated gene names. Since two domains are more likely to have similar GO terms if they are interacting [35], each candidate proteins' GO annotation terms were checked based on the Ipr1's cellular location and its role in biological processes. Those with a GO annotation term of nuclear and terms of transcription/regulation of transcription/apoptosis or child terms of these annotations were kept.…”
Section: Resultsmentioning
confidence: 99%
“…Existing computational methods use varying approaches to tackle different aspects of these problems, each with its own set of aims, strengths, and limitations [18-30]. For example, some methods use additional biological information, such as gene expression data, to establish whether a PPI can occur [24,25,29], and others limit the PPI coverage to smaller sets of high-confidence interactions [19,26,27]. An additional promising approach is to use a feature selection algorithm to find a set of DDIs that best discriminate between true and false PPIs [30].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of protein interaction, such domains and peptides act as recognition elements; we refer to these binding domains or recognized peptides simply as 'domains' in this study. Over the past few years with developments of highthroughput PPI detection technologies, many researchers have shown an interest in extracting domain-domain interactions (DDIs) from large-scale PPI data by statistical methods, demonstrating that the idea of DDIs explain the cause of PPIs in some measure (Sprinzak and Margalit 2001;Riley et al 2005;Singhal and Resat 2007;Liu et al 2009). Here, we statistically extracted DDIs from integrated PPI data of Arabidopsis by following a procedure described in the 'Method' section.…”
Section: Significant Domain-domain Interactions Extracted From Ppi Datamentioning
confidence: 99%
“…These studies have reported that the densely connected regions in a network correspond to known protein complexes or protein functional units. The other approach is the analysis of DDIs coming out from PPI data by statistics or machine learning intended to predict unknown PPIs (Sprinzak and Margalit 2001;Riley et al 2005;Singhal and Resat 2007;Liu et al 2009). These studies have shown that the concept of DDIs statistically extracted from large-scale PPI data can explain the makeup of PPIs to some extent.…”
mentioning
confidence: 99%